Analisis Kemampuan Koneksi Matematis Siswa SMK pada Materi Matriks ditinjau dari Self Efficacy - Titi Rohaeti; Hidayati Nadiah; Rifqi Hidayat (Program Studi S1 Matematika UNESA, 2023)
Mathematical connection ability is one of the important skills in learning mathematics. When students are able to relate mathematical ideas, their understanding of mathematics deepens and lasts longer. Based on the data in the field, it was found that students were still unable to recognize and relate mathematical ideas. During mathematics learning, behaviors that lead to math anxiety and lack of self-confidence were also found. The purpose of this study is to analyze students' mathematical connection abilities in terms of self-efficacy and mathematics anxiety. This type of research is a descriptive qualitative research using mathematical connection test aids, self-efficacy questionnaires, and mathematics anxiety questionnaires to collect data. The subjects in this study were 6 students of SMK majoring in TBSM. The results showed that students who have high, medium, and low self-efficacy can meet 3 indicators of mathematical connection ability.